Returning to the question of a wage premium for returning migrants - Alan Barrett; Jean Goggin (Institute for the Study of Labor (IZA), 2010)
Using data from a large-scale survey of employees in Ireland, we estimate the extent to which people who have emigrated from Ireland and returned earn more relative to comparable people who have never lived abroad. In so doing, we are testing the hypothesis that migration can be part of a process of human capital formation. We find through OLS estimation that returners earn 7 percent more than comparable stayers. We test for the presence of self-selection bias in this estimate but the tests suggest that the premium is related to returner status. The premium holds for both genders, is higher for people with post-graduate degrees and for people who migrated beyond the EU to the US, Canada, Australia and New Zealand. The results show how emigration can be positive for a source country when viewed in a longer term context.
Keywords: J61; O15; 330; Return migration; Ireland; brain drain; brain circulation; Rückwanderung; Bildungsertrag; Internationale Wanderung; Bildungsinvestition; Irland